2014
DOI: 10.1093/aje/kwu182
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Self-Reported Smokeless Tobacco Use by Measurement of Serum Cotinine Concentration Among US Adults

Abstract: Although investigators have assessed the relationship between self-reported cigarette smoking and biomarker levels, the validity of self-reported information on smokeless tobacco (SLT) use is uncertain. We used aggregated data from the 2003–2004, 2005–2006, 2007–2008, and 2009–2010 administrations of the National Health and Nutrition Examination Survey (NHANES) to compare self-reported SLT use with serum concentrations of cotinine, a metabolite of nicotine, among US adults aged ≥18 years. Receiver operating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…First, information on the type of tobacco product used was self-reported and may be subject to reporting bias; however, previous studies have indicated that self-reported estimates of cigarettes and smokeless tobacco are valid. 36,37 Second, self-reported secondhand smoke exposure was used, which could have resulted in misclassification of exposure. However, self-reported secondhand smoke exposure has been previously validated and was significantly correlated with measured cotinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…First, information on the type of tobacco product used was self-reported and may be subject to reporting bias; however, previous studies have indicated that self-reported estimates of cigarettes and smokeless tobacco are valid. 36,37 Second, self-reported secondhand smoke exposure was used, which could have resulted in misclassification of exposure. However, self-reported secondhand smoke exposure has been previously validated and was significantly correlated with measured cotinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…They also did not find significant differences between smokeless tobacco users and nonusers with the exception of NNAL and some polyaromatic hydrocarbons. More recently, Agaku and King (18) used 2003-2010 NHANES data to assess the relationship between self-reported smokeless tobacco use and serum cotinine concentrations and identify the optimal cutpoint for identifying smokeless tobacco users based on cotinine concentrations. Agaku, Vardavas, and Connolly (19) conducted a similar analysis for NNAL using 2007-2010 data.…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study by Agaku et al found a high level (>95%) of concordance between self-reported STP use and serum cotinine levels in US adults. 67 It is also important to note that STP use was assessed differently in 2014 compared to 2015/2016. In 2014, assessment of current STP use was preceded by questions related to STP awareness and ever use, whereas the 2015/2016 surveys only assessed past 30-day use of STPs.…”
Section: Discussionmentioning
confidence: 99%